Free speech attitudes of Nigerian university students at National Universities Games Association event in Benin, Edo State, Nigeria (2014)
This research adopted a descriptive survey design with the use of self-reported instruments to generate data and responses from the research participants. The setting of the study was the main campus of the University of Benin, Edo State, Nigeria where the 23rd edition of the Nigerian Universities Games (NUGA) took place in 2011. The independent variables of the research were socio-economic status, political orientation, age, and gender. The dependent variable was desire for freedom of speech or-free speech attitudes (FSA)and this was measured in line with each of the respondent's score on a 20-item, 3-point Likert questionnaire which measured Freedom of Speech. One hundred and fifteen (115) Nigerian athletes consisting of 70 males and 45 females and aged between 18 and 38 were involved in the study. Males constituted 60.87% while females accounted for 39.1%. Their mean age was 23.57 (SD = 5.34). Due to the fast pace of activities and time pressure at the venue of the games, it was not easy to get hold of athletes to participate in the study; hence the accidental sampling method was used. Thirty four of the respondents reported being liberal in political orientation, 36 reported being moderate, and 45 reported being conservative in political orientation. Political orientation was assessed by Peterson (2007)'s political orientation scale. Participants were of different socioeconomic backgrounds. In relation to the variables studied, four hypotheses were tested using simple Pearson correlation, independent t-test, and one-way ANOVA. Results showed that age positively correlated with FSA significantly while political orientation significantly influenced FSA. Results also showed that gender and socio-economic status did not significantly influence FSA. Discussion centered on the way and manner that FSA and factors influencing it can be studied, understood and put to productive use. Specifically, age and political orientation identified as very important factors influencing FSA. It was concluded that age and political orientation are important variables in shaping FSA and a better understanding of them will partly lay a good foundation for citizens' contribution to democratic growth and good governance.